25th Anniversary Article: No Assembly Required: Recent Advances in Fully Conjugated Block Copolymers. (23rd September 2013) - Robb, Maxwell J.; Ku, Sung‐Yu; Hawker, Craig J.
<x xml:space="preserve">Abstract</x> Fully conjugated block copolymers have emerged as promising materials that combine semiconducting properties with the ability to self‐assemble at the nanoscale. The convergence of these two features has tremendous implications for a number of fundamental molecular assembly and transport questions, while also offering unique advantages for a variety of applications. For example, a nanostructured active layer in organic photovoltaic (OPV) devices may provide for efficient charge separation while simultaneously affording continuous, unimpeded pathways for charge carriers to migrate to their respective electrodes within each individual microphase. This review details the recent progress made in the preparation and application of fully conjugated block copolymers and serves as a comprehensive reference for the materials that have been reported in the literature to date. Focus is placed on fully conjugated block copolymers prepared using chemistries that are relevant to high‐performance polymers in organic electronics research, for example Stille, Suzuki–Miyaura, and Yamamoto coupling.